Causes and environmental implications of increased UV-B radiation - Hester, R. E.; Harrison, Roy M., 1948- (Royal Society of Chemistry, 2000)
Since the realisation that the ozone layer protecting the earth is suffering massive depletion, atmospheric science has been increasingly in the spotlight. It is recognised that we need to increase our knowledge and understanding of the likely impact that increases in UV-B radiation will have on life on earth. Charting research that encompasses the changing distribution of atmospheric ozone, changes in UV-B radiation and the consequent effects on photochemistry and biological systems in the aquatic and terrestrial environments, Causes and Environmental Implications of Increased UV-B Radiation draws together experts from the international community. Also included is a discussion of the emotive and highly topical subject of skin cancer as related to increased UV-B radiation. As an up-to-date and authoritative summary of the state of this highly complex science, this book will be welcomed by all practitioners and researchers in the field.
Keywords: Ozone layer depletion.; Ultraviolet radiation -- Environmental aspects.; elektronické knihy; electronic books